2007
DOI: 10.2176/nmc.47.509
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cavernous Malformation Within Vestibular Schwannoma: Immunohistochemical Analysis of Matrix Metalloproteinase-2 and -9 -Case Report-

Abstract: A 65-year-old man presented with a rare case of cavernous malformation with hemorrhage located within vestibular schwannoma. He had suffered hearing impairment for 20 years, and was admitted to our hospital with vertigo and ataxic gait. Neurological examination revealed hearing loss, facial nerve paresis, and left cerebellar ataxia. Magnetic resonance imaging demonstrated a left vestibular schwannoma 35 mm in diameter, as well as a heterogeneous area associated with hypointense rim within the tumor, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…MMP2 is a type IV collagenase and is secreted as a zymogen, which is then proteolytically processed to the active form, which contributes to degradation and damage of the extracellular matrix and basement membrane. Therefore, this promotes tumor cell infiltration of the surrounding tissues by breaking through the basement membrane, ultimately leading to tumor cell invasion and metastasis ( 6 , 7 ). Previous studies have indicated that MMP2 is expressed in a variety of tumor cells, and is associated with tumor cell growth, invasion and metastasis ( 2 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…MMP2 is a type IV collagenase and is secreted as a zymogen, which is then proteolytically processed to the active form, which contributes to degradation and damage of the extracellular matrix and basement membrane. Therefore, this promotes tumor cell infiltration of the surrounding tissues by breaking through the basement membrane, ultimately leading to tumor cell invasion and metastasis ( 6 , 7 ). Previous studies have indicated that MMP2 is expressed in a variety of tumor cells, and is associated with tumor cell growth, invasion and metastasis ( 2 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fujimara et al 10 performed immunohistochemistry for MMP-2, MMP-9, and TIMP-s on surgical specimens from 7 patients with known hemorrhagic cerebral cavernous malformations. 13 All 7 demonstrated strong expression of all 3 markers on the endothelial cells of these lesions, without expression in adjacent normal brain. The conclusions suggested that the expression of these molecules can contribute to the vascular instability within these lesions, conceptually similar to the activity of these molecules within aggressive tumors digesting endothelial basal laminae to maintain their blood-brain barrier permeability.…”
Section: Discussionmentioning
confidence: 89%
“…In 2007, Sakata et al 13 reported on a patient with a cavernous malformation which after resection was found to avidly express MMP-2 and MMP-9. Fujimara et al 10 performed immunohistochemistry for MMP-2, MMP-9, and TIMP-s on surgical specimens from 7 patients with known hemorrhagic cerebral cavernous malformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral CMs are associated with other cerebrovascular lesions including vascular malformations, sinus thrombosis, 5) moyamoya disease, 10) and brain tumors. 19) However, association with dural arteriovenous fistula (dAVF) is extremely rare. 5,11) Here we report a case of recurrent dAVF associated with orbital CM, which was not evident at the initial operation for dAVF.…”
Section: Introductionmentioning
confidence: 99%